Salinity and pH effects on floating and emergent macrophytes in a constructed wetland - Hadad, Hernán Ricardo (2017)
Salvinia herzogii, Pistia stratiotes and Eichhornia crassipes (floating species) were the dominant macrophytes in a constructed wetland (CW) over the first years of operation. Later, the emergent Typha domingensis displaced the floating species, becoming dominant. The industrial effluent treated at this CW showed high pH and salinity. The aim of this work was to study the tolerance of floating species and T. domingensis exposed to different pH and salinity treatments. Treatments at pH 8, 9, 10 and 11 and salinities of 2,000; 3,000; 4,000; 6,000 and 8,000 mg L-1 were performed. Floating macrophytes were unable to tolerate the studied pH and salinity ranges, while T. domingensis tolerated higher pH and salinity values. Many industrial effluents commonly show high pH and salinity. T. domingensis demonstrated to be a suitable macrophyte to treat this type of effluents.